2019
DOI: 10.3390/app9091926
|View full text |Cite
|
Sign up to set email alerts
|

Nanosized Ni/SBA-15 Catalysts for CO2 Reforming of CH4

Abstract: Ni, Co, and Co–Ni bimetallic catalysts supported over SBA-15 and over SBA-15 doped with Zn or Ce oxides were prepared and tested in a methane dry reforming reaction. The loading of the metals in the catalyst was 5 wt % for either mono or bimetallic catalysts. The prepared catalysts were tested in a continuous-flow fixed-bed reactor at 800 °C under atmospheric pressure. XRD, TPR, TPD, and SEM characterization techniques were employed to investigate the catalytic properties of fresh catalysts. SEM and TGA were u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…The same effect was reported by Ibrahim et al , 89 which indicated that Ni sintering was easier than Al and Co, and alloying with other metals was necessary (usually a noble metal, such as Au) to avoid this sintering. It means that nickel formations are probably occupying more mesopore than micropore channels, as can be observed from the pore size distribution (Fig.…”
Section: Resultssupporting
confidence: 80%
“…The same effect was reported by Ibrahim et al , 89 which indicated that Ni sintering was easier than Al and Co, and alloying with other metals was necessary (usually a noble metal, such as Au) to avoid this sintering. It means that nickel formations are probably occupying more mesopore than micropore channels, as can be observed from the pore size distribution (Fig.…”
Section: Resultssupporting
confidence: 80%
“…The synthesis of SBA-15 as a catalyst support in the previous studies , were often performed using the sol–gel method with Pluronic 123 as a template and tetraethylorthosilicate as silica sources. This method requires a considerable time commitment for the hydrolysis–condensation process, which is usually 24 h. In the present study, the synthesis of SBA-15 is conducted using the ultrasonic-assisted sol–gel method for which the hydrolysis–condensation stage is 3 h. The sonication method is used as an alternative to the process of stirring, heating, and vibrating in hydrothermal synthesis .…”
Section: Introductionmentioning
confidence: 99%
“…However, catalysts synthesized using these precious metals cannot be commercialized because of their limited availability and cost [5,6]. Alternatives to these expensive, scarce, precious-metal-based catalysts are Ni-supported catalysts [6][7][8]. On the one hand, Ni is cheap and abundant, in addition to that, its use in catalytic dry reforming of methane reactions has shown promising results.…”
Section: Introductionmentioning
confidence: 99%